Militarism and Education in America - Astore, William J. (Radical Teacher, 2020)
The United States today is marked by a culture that is both militarized and commoditized, in which education has become both an enabler to a state of permanent war and a facilitator of business and industry imperatives. The increasing militarism of America’s schools, colleges, and universities demands a response. Active and informed dissent is what’s required, for nothing is more truly American or patriotic than well-informed dissent that seeks to protect vital liberties. This article suggests several ways that educators can alert students to the twin perils of militarism and an education driven too narrowly by "learn to earn" imperatives.